Bioremediation of hazardous azo dye methyl red by a newly isolated Bacillus megaterium ITBHU01: Process improvement through ANN-GA based synergistic approach - Tripathi A.; Singh Y.; Verma D.K.; Ranjan M.R.; Srivastava S.K. (My University, 2025)
Methyl red (MR), a commonly used azo dye, poses serious environmental consequences due to its toxic, recalcitrant and refractory nature. In the current study, a bacterial isolate, ITBHU01, with remarkable characteristics to decolourize MR dye, was characterized by its phenotypic features and phylogeny using fatty acid methyl ester (FAME) profiling and 16S rDNA sequence homology. At artificial neural network linked genetic algorithm (ANN-GA) based optimal conditions of parameters viz., initial MR concentration of 258.54 mg/L, pH of 7.21, the temperature of 38.2°C, and salinity of 26.3 g/L, the maximum decolourization of 98.1% was obtainedby static incubation of 24 h. FTIR spectra revealed the bacterial degradation of MR dye by cleavage of azo bonds present in the dye. ESI-MS analyses have shown formation of two prime metabolic products as N, N-dimethyl-p-phenylenediamine and 2-aminobenzoic acid indicating the symmetric cleavage of azo (-N=N-) bond; however, the presence of additional peaks illustrated about the formation of different other metabolites also. Purified azoreductase with a molecular weight of 28.0±0.2 kDa was found primarily responsible for reductive cleavage of azo bond leading to biodegradation of MR. Phytotoxicity assay for bacterial treated dye on seeds of Solanum lycopersicum, Sorghum bicolor and Triticum aestivum had significantly shown that there was no inhibition in their seed germination confirming the non-toxic nature of degraded metabolites. © 2017 National Institute of Science Communication and Information Resources (NISCAIR). All rights reserved.